When learning becomes a fetish: the pledge, turn and prestige of magic tricks. (3rd July 2018) - Bainbridge, Alan; Gaitanidis, Anastasios; Hoult, Elizabeth Chapman
Abstract: It is our contention that the process of higher education could be read as a commodity and in both Marxian and Freudian assumptions, a fetish. Instrumental in this discussion are Marx's theorising of the commodity fetish that deceives by conflating the distinction between use and exchange value; and Freud's re-visiting of his theory of fetishism, where he considers the fetish in the context of dealing with separation and loss in everyday life. This paper highlights how the consequence of fetishised behaviour has led to violent outcomes, such as the policy decision in England to introduce a 'Teaching Excellence Framework' (TEF). We argue that the TEF may bring about the death of learning in HE and diminish the role of academic staff. Nevertheless, influenced by Winnicott, Cixous and Biesta, we offer a more hopeful 'Teaching that is Good Enough Framework'.